2013
DOI: 10.1148/radiol.12121216
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Mammography: Identifying Minimally Acceptable Interpretive Performance Criteria

Abstract: Purpose:To develop criteria to identify thresholds for the minimally acceptable performance of physicians interpreting diagnostic mammography studies. Materials and Methods:In an institutional review board-approved HIPAA-compliant study, an Angoff approach was used to set criteria for identifying minimally acceptable interpretive performance for both workup after abnormal screening examinations and workup of a breast lump. Normative data from the Breast Cancer Surveillance Consortium (BCSC) was used to help th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 17 publications
(22 reference statements)
0
31
0
Order By: Relevance
“…Despite variability in performance measures, on average, radiologists who worked up fewer recalled mammograms had consistently lower sensitivity, CDRs, and FPRs at any given total volume. Current U.S. Food and Drug Administration regulations require U.S. physicians to have interpreted 960 [11] 43 [12] 47 [10] 129 [11] 32 [18] 86 [17] 101 [8] Progesterone receptor status* Negative 432 (25) 83 (27) 81 (20) 268 (26) 38 (27) 109 (26) 285 (24) Positive 1297 (75) 220 (73) 332 (80) 745 (74) 104 (73) 306 (74) 887 (76) Unknown 232 [12] 45 [13] 47 [10] 140 [12] 36 [20] 86 [17] 110 [9] Note.-Numbers in parenthese are column percentages. Percentages in brackets (for unknown variables) were not included in total column percentages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite variability in performance measures, on average, radiologists who worked up fewer recalled mammograms had consistently lower sensitivity, CDRs, and FPRs at any given total volume. Current U.S. Food and Drug Administration regulations require U.S. physicians to have interpreted 960 [11] 43 [12] 47 [10] 129 [11] 32 [18] 86 [17] 101 [8] Progesterone receptor status* Negative 432 (25) 83 (27) 81 (20) 268 (26) 38 (27) 109 (26) 285 (24) Positive 1297 (75) 220 (73) 332 (80) 745 (74) 104 (73) 306 (74) 887 (76) Unknown 232 [12] 45 [13] 47 [10] 140 [12] 36 [20] 86 [17] 110 [9] Note.-Numbers in parenthese are column percentages. Percentages in brackets (for unknown variables) were not included in total column percentages.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not always the case. It is possible to improve both measures to the point where improvements in one measure reach a threshold beyond which the other is diminished (20). Thus, increases in FPRs associated with the improvement in sensitivity and CDRs potentially could Figure 1: (continued) (d-f) Graphs show multivariable adjusted screening performance measures according to work-up of any recalled screening mammograms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously established criteria for acceptable interpretive performance of screening mammography, evaluating multiple performance measures separately: specifically sensitivity, specificity, cancer detection rate (CDR), recall rate, and positive predictive value of recall (PPV 1 ) [4, 5]. We suggested that a radiologist not meeting the criteria for at least one measure should be advised to examine their data in the context of their specific clinical practice and consider additional, focused continuing medical education to improve performance if appropriate [5, 6]. However, considering these performance measures together is more clinically meaningful, because they are inter-related, resulting in trade-offs between recalling patients for further work-up and detecting cancer [7].…”
Section: Introductionmentioning
confidence: 99%
“…Expert panels have been used for decades to establish benchmarks and guidelines for breast imaging [4–6, 8]. …”
Section: Introductionmentioning
confidence: 99%